Práticas docentes e a instituição de relações democráticas entre professor e alunos - Espósito, Laura Natália Coelho (2020)
This work presents, from the speech of a teacher, which elements of teaching practice indicate the presence or absence of democratic relations in the teacher-student relationship. We started from the hypothesis that the investigated teacher could reveal, in her speech, some nondemocratic elements in the interaction with her students. We proceeded to qualitative research, with documentary analysis and interview, carried out with a regent teacher of the 4th year of elementary school - initial years, who works in a public school. The theoretical framework included authors such as Vinha (1999), Benevides (1996), Silva (2016), Araújo (2000) and Libâneo (2012; 2016), in addition to official documents and online platforms, such as the 1988 Federal Constitution, Guidelines Law and Bases of Brazilian Education, National Education Plan, State Education Plan, and PNE Observatory. The analysis made it possible to confirm the initial hypothesis of this research: the investigated teacher revealed, at times, non-democratic elements, in the interaction with her students, showing difficulty in imposing limits on her students or having contradictory attitudes in addressing issues of behavior and relationship between students. At the same time, the teacher indicated to enable her students to make decisions, was open to dialogue and said to collectively elaborate the group's arrangements, emphasizing, in her speeches, her purposes of maintaining respect and interchange with her students and other school professionals. We point out the role of management for this contradictory performance of the teacher in the classroom. Because, despite the Political Pedagogical Project of the school in which the teacher works to explain the principle of democratic management - with participation, dialogue and sharing of decisions, between families, teachers, students and other actors of the educational institution -, we infer that the direction does not act in a way to assist the faculty to maintain this type of interaction with their students. Given the challenges presented by the educator, it is clear the role that teacher education, initial and continuing, must-have, to contribute to teaching focused on democratic values, necessary for living in a democratic society, to promote development full of students, aiming to make them critical and reflective citizens, capable of significant interventions for the construction of a democratic society